THE IMPORTANCE OF THE USE OF E- LOGISTICS IN THE LOGISTICS SECTOR: A REVIEW ON ANTALYA FREE ZONE COMPANIES (Third Sector Social Economic Review, 2023)
It is seen that the importance of e-commerce in terms of logistics service providers has become a necessity to use electronic-based applications in logistics management in order to keep up with the dynamic changes in the world and meet customer requirements. Electronic-based transactions with information technologies require redefining logistics activities. According to the scope of the study, while the companies located in Antalya Free Zone are determined as samples, survey application is carried out as the method of research. The main purpose of the study is to evaluate the advantages and disadvantages of e-logistics activities in the logistics infrastructures owned by the companies in Antalya Free Zone in order to gain competitive advantage with their usage levels. Within the scope of the study, the model and the hypotheses developed were evaluated using Ki-Square homogeneity test and Anova test. Anova test results were also applied to Tukey and Scheffe tests. The main finding of the research is that companies that benefit from e-logistics services where “Barcode/RFID, WMS and vehicle Tracking Systems” applications make a difference have a competitive advantage and have a competitive advantage in terms of value chains. The research results show that the use of advanced logistics operators can help firms to increase their competitiveness in today’s market.
Keywords: Logistics Sector; Logistics Management; Information Operating Systems; E- Logistics; Antalya Free Zone.